2005
DOI: 10.1016/j.jacc.2004.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Infarct morphology identifies patients with substrate for sustained ventricular tachycardia

Abstract: Infarct surface area and mass, as measured by cardiac MRI, are better identifiers of patients who have a substrate for MVT than LVEF. Further evaluation of infarct size characterization by cardiac MRI as a predictor of sudden cardiac death is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
302
3
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 434 publications
(328 citation statements)
references
References 36 publications
16
302
3
7
Order By: Relevance
“…Indeed, multiple studies have linked VT with increased infarct size or reduced LVEF. 2,9,17,23 Our study indicates that infarct size and ventricular arrhythmia are also strongly correlated in the setting of primary PCI.…”
Section: Multivariate Analysismentioning
confidence: 59%
See 1 more Smart Citation
“…Indeed, multiple studies have linked VT with increased infarct size or reduced LVEF. 2,9,17,23 Our study indicates that infarct size and ventricular arrhythmia are also strongly correlated in the setting of primary PCI.…”
Section: Multivariate Analysismentioning
confidence: 59%
“…Furthermore, early reperfusion ensues a reduced infarcted and ischaemic area, reducing the risk of associated trigger activity leading to arrhythmia. 17,18 Reduction and rapid wash out of ischaemic toxic by-products may also be of importance. Implementation of optimal facilitation of primary PCI is a topic of growing clinical importance.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…In coronary artery disease, Bello et al 27 showed that fibrosis measured by CMR in infarcted areas are better identifiers of patients who have a substrate for monomorphic ventricular tachycardia than LV ejection fraction.…”
Section: Fig 4 -A Patient Example With Hypertrophic Cardiomyopathy mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Discrepancies between observations with different diagnostic techniques may reflect the fact that LV geometry and function after the MI result from a complex interaction of various factors, including successful early revascularization 10) which may limit unfavorable adaptive changes of the myocardium. [11][12][13] The effect of successful early revascularization on the relationship between infarct tissue characteristics versus LV remodeling is not completely known.…”
mentioning
confidence: 99%
“…While some investigators found significant correlations between infarct tissue characteristics and LV remodeling in patients with successful early revascularization, 2,4,5,[14][15][16] others found conflicting results in more heterogeneous study populations (Table I). 3,6,8,9,[17][18][19] Cardiovascular magnetic resonance (CMR) imaging in combination with the contrast enhancement (CE) technique allows accurate assessment of LV geometry and function as well as tissue characteristics such as size, heterogeneity, and transmurality of the myocardial scar. [20][21][22] In the present study, we investigated the relation between infarct tissue characteristics and LV remodeling in patients with versus without successful early revascularization in a population of consecutive patients who underwent CE-CMR examination.…”
mentioning
confidence: 99%